Structural Racism, Place, and COVID-19: A Narrative Review Describing How We Prepare for an Endemic COVID-19 Future - Estrada, Leah V.; Levasseur, Jessica L.; Maxim, Alexandra; Benavidez, Gabriel A.; Pollack Porter, Keshia M. (Health equity, 2022)
Place is a social determinant of health, as recently evidenced by COVID-19. Previous literature surrounding health disparities in the United States often fails to acknowledge the role of structural racism on place-based health disparities for historically marginalized communities (i.e., Black and African American communities, Hispanic/Latinx communities, Indigenous communities [i.e., First Nations, Native American, Alaskan Native, and Native Hawaiian], and Pacific Islanders). This narrative review summarizes the intersection between structural racism and place as contributors to COVID-19 health disparities. This narrative review accounts for the unique place-based health care experiences influenced by structural racism, including health systems and services and physical environment. We searched online databases for peer-reviewed and governmental sources, published in English between 2000 and 2021, related to place-based U.S. health inequities in historically marginalized communities. We then narrate the link between the historical trajectory of structural racism and current COVID-19 health outcomes for historically marginalized communities. Structural racism has infrequently been named as a contributor to place as a social determinant of health. This narrative review details how place is intricately intertwined with the results of structural racism, focusing on one's access to health systems and services and physical environment, including the outdoor air and drinking water. The role of place, health disparities, and structural racism has been starkly displayed during the COVID-19 pandemic, where historically marginalized communities have been subject to greater rates of COVID-19 incidence and mortality. As COVID-19 becomes endemic, it is crucial to understand how place-based inequities and structural racism contributed to the COVID-19 racial disparities in incidence and mortality. Addressing structurally racist place-based health inequities through anti-racist policy strategies is one way to move the United States toward achieving health equity.